CONFLICT POTENTIAL OF THE WAHABIAN COMMUNITIES IN THE WESTERN BALKANS AREA - Mijalković, Saša; Baškalo, Duško; Baškalo, Duško (Serbian political thought, 2024)
The Western Balkans have historically confirmed predispositions for the development of radical Islamism, and in recent times, especially through Wahhabi communities and parajams. In this regard, the aim of the paper is to analyze the history of the spread of Wahhabism and radical Islam in the Western Balkans and the conditions that contributed to the creation of Wahhabi communities. Also, the goal is to determine how much of a security threat the Wahhabi communities pose to the Western Balkans and what are the goals of the radical Islamists who create and commit these communities. Ultimately, the goal is to identify/map potential conflict zones. Key words: Wahhabis, radical Islamism, parajammats, political violence, Western Balkans.